ANALISA USAHA DOMBA LOKAL DENGAN WAKTU PEMBERIAN PAKAN DAN PANJANG PEMOTONGAN BULU YANG BERBEDA - Aisyah Nurmi (Universitas Muhammadiyah Tapanuli Selatan, 2017)
This research was conducted in Unit Resettlement The Nucleus Enterprise System (NES) of LivestockBarumun District of AekNabaraBarumun Padang Lawas regency, lasts for three months. There were 24 local sheep with initial average body weight 15,91 ± 3,69 kg were used in this research.Design of this experiment was completely randomized design factorial with factor A was feeding time (A1 = feeding at 08.00 and 16.00, A2 = the evening feeding time at 20.00 and 04.00 pm ), and factor B was shearing (B1=0 cm, B2=1 cm, B3=2 cm, B4=natural).The aim of thisresearchwas to analysis the effort from the utilization of feeding time and shearing towards the effort analysis of local sheep that seem from the sum production cost, the sum of production income, profit and loss, benefit cost ratio, break even point of production price and break even point of production volume, income over feed cost and return on investment. The results showed that feeding time was very significant (P <0.01) to total production, profit-loss, B / C ratio and Break Even Point Price, significantly different (P <0.05) to total production cost and IOFC and no effect real (P> 0.05) to BEP Volume; (P0.05) to total production, profit and loss, B / C ratio, BEP Volume, BEP Price and IOFC but not significantly different (P> 0.05) to total production cost; the interaction of feeding and cutting treatments had significant effect (P <0.05) on total production cost and BEP Volume but no significant effect (P> 0.05) on total production, profit loss, B / C ratio, BEP price and IOFC. The conclusion of this study is that the treatment of 2 cm cutting and night feeding of local sheep is the best, with no major differences in B / C ratio and profit-loss, and economically profitable.Based on the result of the research, it can be concluded that the difference of feeding time and length of cutting feathers affect the local sheep business analysis. Treatment of 2 cm cutting of the feathers and the provision of feed at night to local sheep provide the best results, and economically profitable.